RANCANG BANGUN ALAT PENYIRAMAN TANAMAN DENGAN POMPA OTOMATIS SISTEM IRIGASI TETES PADA LAHAN KERING: (Design Tools Watering Plants With Automatic Pump to Drips Irrigation System For Dry Land) - Amuddin Amuddin; Joko Sumarsono (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2015)
This study aims to (1) Designing wake automatic watering equipment on dry land, (2) Determine the effective and efficient manner, (3) Knowing more specific performance in the use of electrical power. The benefits of this research (1) automated tool that can help overcome the shortage of water in the dry season in dry land, (2) helping farmers in overcoming problems crop irrigation in the dry season / dry, (3) scientific knowledge in automation watering drip irrigation system with pump solar energy as renewable energy. The research was conducted in the village of Batu Layar Sandik District of West Lombok in April 2011 to October 2011. This study uses an experimental method with the following steps: (a) Stage Design, (b) the assembly stage and followed by (c) Phase characterization automatic watering tool. At the stage of design executed by: measuring the ambient temperature (0C), measure wind speed (km / h), determine to what size of pump power (watts); followed by stages of assembly. Then proceed with step kerakterisasi automatic watering tool in the characterization of applying completely randomized design (CRD) factorial design composed 8 treatment. The first factor is the rotation of the motor pump with 4 variations of rotation, namely (1600, 1800, 2200 and 2400 rpm). Each treatment each repeated 3 times. While the provision of irrigation water treatment drops on each network is divided into blocks, namely (I, II, III and IV blocks) are taken based on the treatment of the above factors. Each treatment was observed parameters-parameters of chilli crop water requirements. The parameters characterizing automatic sprinklers include: efficiency of crop water requirements and water use efficiency in total. Results showed (1) automatic watering device can regulate the amount and uniformity of discharge of water droplets in every hole in the use of water for plants drip irrigation system with an average of (± 0.5632 liters /crop), the one-time watering at each plants with 2400 rpm motor pump. (2) System drip irrigation watering holes aimed directly at the plant, the amount of water used is very small. So that the area can be watered plants covering an area of ​​1.74 mx 2.09 m = 3.6366 m2 / plot. With a total land area is tested for this type of tomato plant and a land area of ​​39.78 ± m2 for the type of chilli plants, bringing the total land area of ​​± 68.21 m2 on the pump discharge position of ±72.50578 liters/minute, and then flowed through 6 Fruit of the pipeline with the average number ±12.084297 liters perpipe on each plot. While in the pipeline, there are 16 pieces of water drain holes are directed at each plant to remove water in the respective holes per hole ± 0.755268542 liters/minute. (3) The electric power is used to drive the pump motor in this study is similar to the output ±0.336796 HP the uotput equal to ±0.336796 HP x 0.7457 kWatt = 251.25 watts, where as the unused power of ± 1.333333 watts with efisiensin power to the pump motor power calculation is divided power is used together with efficiency = 251.25 watts/1.333333 watts x 100% = 18843.75%.